P-363 Systematic review and meta-analysis of female lifestyle factors and risk of recurrent pregnancy loss (RPL). (30th June 2022) - Ng, K.Y.B; Cherian, G; Kermack, A.J; Bailey, S; Macklon, N; Sunkara, S.K; Cheong, Y
Abstract: Study question: What is the impact of female lifestyle (BMI, smoking, caffeine, alcohol) on RPL in the general population and on further miscarriage in the RPL population? Summary answer: Being underweight and BMI>25 contributes significantly to increased risk of RPL (general population). BMI>25 or BMI>30 increases the risk of further miscarriages (RPL population) What is known already: Lifestyle factors are modifiable and in many instances lifestyle optimisation enhances the chances of a positive reproductive outcome. Whilst the specific mechanisms leading to early pregnancy loss is still relatively unknown, poor lifestyle is associated with a hostile reproductive environment whereby optimal embryo implantation and securement of a pregnancy is compromised. The peri-implantation intrauterine environment is a key determinant of pre-implantation embryo development and early programming. RPL is a complex disease where causation has been attributed to numerous factors and whilst it is known that lifestyle factors affect sporadic miscarriage, the extent of this on RPL is less well known. Study design, size, duration: A systematic review and meta-analysis was performed to assess the associations between lifestyle factors and RPL. Studies that analysed RPL in the context of BMI, smoking, alcohol and caffeine intake were included. The primary and secondary outcomes were odds of having RPL in the general population and odds of further miscarriage, respectively. Participants/materials, setting, methods: Studies were included if they explored women of reproductive age who had been exposed to an aspect of female lifestyle. We excluded studies which assessed the effectiveness of an intervention aimed at altering lifestyle and studies which assessed lifestyle factors in the context of IVF outcomes or associations with PCOS. We screened all studies, reviewing full papers where required and disregarding those that did not meet the eligibility criteria using a double-blind approach. Main results and the role of chance: The systematic search identified a total of 24, 705 records and an additional 194 records through hand-searching of references. 16 studies were included in this systematic review and meta-analysis. None of these studies were RCTs; there were 8 case control studies, 6 cohort studies, 1 survey-based study and 1 cross-sectional study. Underweight and women with BMI > 25 are at higher odds of RPL in the general population (OR 1.2, 95% CI 1.12–1.28 and OR 1.21, 95% CI 1.06–1.38, respectively). In women with RPL, having BMI > 30 and BMI > 25 has increased odds of further miscarriages (OR 1.77, 95% CI 1.25–2.50 and OR 1.35, 95% CI 1.07–1.72, respectively). The odds of RPL in the general population is increased in women who were cigarette smokers compared to non-smokers but this is not statistically significant (OR 1.62, 95% CI 0.90–2.93). Alcohol intake compared with no alcohol intake increases the risk of RPL, however this is not statistically significant (OR 1.12, 95% CI 0.88–1.44). The odds of RPL in the higher caffeine intake group (>99mg/day) compared to the lower caffeine intake group (≤99mg/day) is higher but not significant (OR 1.35, 95% CI 0.83–2.19). Limitations, reasons for caution: The quality of the evidence was low or very low, mainly due to heterogeneity in study populations. There were inconsistencies in the definition of RPL, some studies included women with '≥3 consecutive miscarriages', others '≥2 miscarriages'. We did not explore the impact of male lifestyle on the risk of RPL. Wider implications of the findings: Being underweight and BMI>25 contributes significantly to increased risk of RPL. BMI>25 or BMI>30 increases the risk of further miscarriages in the RPL population. Studies addressing the effects of alcohol, cigarette smoking and caffeine on the risk of RPL with optimisation of BMI in this cohort of women are warranted. Trial registration number: Is the frequency of low plasma-mannose-binding lectin (p-MBL) levels increased in recurrent pregnancy loss (RPL) after spontaneous conception or IVF/ICSI and recurrent implantation failure (RIF)?